PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS IX SMPN 13 SIJUNJUNG - -, Aiqozni (STKIP PGRI Sumbar, 2014)
The problems found are students embarrassed and did not want to ask questions about material that is not yet understood, as well as a lack of understanding of mathematical concepts students of class IX SMP 13 Sijunjung. This study aims to determine whether students understanding of mathematical concepts by applying active learning strategies Learning type Start With A Question (LSQ) is better than the students understanding of mathematical concepts that apply conventional teaching students of class IX SMP 13 Sijunjung. This research is an experimental study. The study population was 13 students of class IX SMP Sijunjung. The sampling technique is random, the selected class is a class IX.2 as the experimental class and the control class as a class IX.3. The instrument used was the ultimate test with the indicator of understanding the concept. The form of the test used was 0.742 essay with reliability. On average students understanding of the concept of an experimental class 71.10 with a standard deviation of 13.36 and an average grade control with standard deviation 62.82 12.97. Hypothesis testing is done with the t test of the parties. Students final test result data processed with the help of Minitab software, the value of the P-value = 0.043. It appears that P-value <Î±. The hypothesis is accepted so that the real level Î± = 0.05. So it is concluded that the students understanding of mathematical concepts to the application of active learning strategies Learning type Start With A Question (LSQ) is better than the students understanding of mathematical concepts with the application of conventional learning class IX students SMP 13 Sijunjung academic year 2014/2015.